Is There a Trade-off Between Quality and Profitability in United States Nursing Homes?. Issue 2 (April 2017) - Godby, Tyler; Saldanha, Sarah; Valle, Jazmine; Paul, David P.; Coustasse, Alberto
Abstract : Nursing home residents across the United States rely on quality care and effective services. Nursing homes provide skilled nurses and nursing aides who can provide services 24 hours a day for individuals who could not perform these tasks for themselves. Not-for-profit (NFP) versus for-profit (FP) nursing homes have been examined for utilization and efficacy; however, it has been shown that NFP nursing homes generally offer higher quality care and generate greater profit margins compared with FP nursing homes. The purpose of this research was to determine if NFP nursing homes provide enhanced quality care and a larger profit margin compared with FP nursing homes. Benefits and barriers in regard to financial stability and quality of care exist for both FP and NFP homes. Based on the findings of this review, it is suggested that NFP nursing homes have achieved higher quality of care because of a more effective balance of business aspects, as well as prioritizing resident well-being, and care quality over profit maximization in NFP homes.